Synthesis, characterization, and hydrogen storage capacities of polymeric squaric acid complexes containing 1-vinylimidazole - Yilmaz, Hakan; Andac, Omer; Gorduk, Semih (PERGAMON-ELSEVIER SCIENCE LTD, 2017)
In this work, three new polymeric coordination complexes were synthesized using squaric acid and 1-vinylimidazole. The structures of the coordination polymers, formed with Co(II), Zn(II), and Cd(II) ions, were characterized by elemental analysis, infrared spectroscopy (IR), thermal analysis (Thermogravimetry, TG; Derivative Thermogravimetry, DTG; Differential Scanning Calorimetry, DSC), magnetic susceptibility, X-ray powder diffraction, and X-ray single crystal techniques. The X-ray single crystal method showed that the squarato ligand behaves as bis(monodentate) via the oxygen atoms in mu(1,3)-mode and 1-vinylimidazole coordinates to the metal ion via the ring nitrogen atom as monodentate in the complexes. The central ions in the complexes obtained as single crystal exhibited slightly distorted octahedral geometries. The surface areas and hydrogen storage capacities of the synthesized complexes were also examined. (C) 2017 Elsevier Ltd. All rights reserved.
Keywords: Squaric acid; 1-Vinylimidazole; Coordination polymer; Surface area; Hydrogen storage; METAL-ORGANIC FRAMEWORKS; COORDINATION POLYMERS; MAGNETIC-PROPERTIES; CRYSTAL-STRUCTURES; COPPER(II) COMPLEXES; TERPHENYL-2,2',4,4'-TETRACARBOXYLIC ACID; DINUCLEAR COPPER(II); STRUCTURAL DIVERSITY; OXOCARBON DIANIONS; SOLID-STATE; Chemistry; Crystallography